PENGARUH STATUS GIZI DAN KEKUATAN GENGGAMAN TANGAN TERHADAP KEKUATAN TORSI BAUT PADA OPERATOR PERAKITAN STATION BUS ATAU TRUK AC DI PT. DENSO INDONESIA - Falaqullah Dersono Chandradimuka (Dinamika : Jurnal Ilmiah Teknik Mesin, 2022)
Workers are one of the most important elements of the company in order to improve the problem is the company. Work efficiency of workers is highly dependent on their muscle strength where hand grip strength (HGS) determines a person's muscle strength. In this case, PT Denso Indonesia, a company engaged in the automotive sector, really pays attention to the condition of its workers, especially the physical condition, this also applies to assembly operators who must have a strong physical hand grip strength to maintain the quality of the product. Research that discusses the relationship between nutritional status and hand grip strength is still minimal even though it is important in work, especially for assembly operators. Therefore, researchers are interested in knowing the effect of nutritional status on the torsional strength of bolts on bus or truck stations. The method used is the experimental method with a sample of 11 operators while the data is processed by ANOVA. The results obtained from the study are (1) from the 11 correspondent operators sampled by the researcher, the details of nutritional status are as follows: 4 Obesity level 1, 6 Normal and 1 Mild Thiness. (2) In the category of nutritional status OB level 1 the average value of hand grip strength is 44.4 Kg, in the Normal nutritional status category the average value of hand grip strength is 37.33 Kg, Operator nutritional status Mild Thines with 1 person has hand grip strength 37.9 Kg. (3) There is no effect between nutritional status and operator age on hand grip strength and average maximum torque because the F-count < F-table and sig > 0.05.